Processed Food Creations Made From Tempeh - Catherine, Catherine; Eveline, Eveline; Antony, Vincent Setiawan; Juliana, Juliana (International Journal of Social and Management Studies, 2022)
This research is a research that takes processed food products made from tempeh which are introduced in the community as the object of research. This study uses a quantitative method with purposive sampling using a questionnaire containing a hedonic test and a hedonic quality test through the Friedman test. Respondents from this study were 56 consumer panelists which is public societyThe results of this study are based on the fried test, it can be seen the level of panelists' preference for processed tempe products based on aspects that have been determined by the researcher. From the aspect of aroma, processed tempe products in the form of hot pudding are preferred. From the aspect of taste, processed tempe products in the form of tempeh pancakes are preferred by the panelists. From the aspect of texture, processed tempe products in the form of croffles are preferred by the panelists. And from the aspect of appearance, processed tempe products in the form of tempeh pancakes are preferred by the panelists. In general, tempeh creativity products are accepted both in terms of taste, aroma, texture, and appearance. However, the average results given by the panelists are based on the fried test or rating test for a product where the aroma, taste, texture and testing are different in each aspect,where the results of the assessment given by the panelists are influenced by the panelists' thoughts about aroma, taste, texture and appearance by the food of croffles, pizza, burgers, hot puddings, and pancakes that were created before this tempeh processed product existed. So that the taste, aroma, texture and appearance displayed by this tempe processed product were strange for some panelists.